Data protection in working life - Finland. Ministry of Labour (Ministry of Labour, 2004)
"The Act on Protection of Privacy in Working Life (759/2004), subsequently The Act on Data Protection in Working Life will enter into force on 1st October 2004. The Act supplements the former Act on Protection of Privacy in Working Life (477/2001). In the new Act, the provisions of the former Act are the earlier ones as to their content, but the structure of the Act has changed. The Act incorporates provisions on drug tests, camera surveillance and the protection of e-mail. The Personal Data Act (523/1999) and the Act on the Protection of Privacy in Electronic Communications (516/2004) incorporates general provisions relating to data protection which are also applied in working life beside this special Act. This brochure seeks to provide an overall picture of data protection in working life." (Extract from the Introduction)